System-Level Performance Evaluation of Dilithium2, Falcon-512, and SPHINCS+ for Post-Quantum Secure E-Government Document Signing - Rudolf Sinaga; Samsinar Samsinar; Mohd Shahizan Othman (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2026)
Background: The rapid advancement of quantum computing threatens the cryptographic foundations of e-Government infrastructure, particularly classical public-key algorithms susceptible to Shor's algorithm. Post-Quantum Cryptography (PQC) offers a viable pathway for securing digital signature systems against emerging quantum adversaries. Objective: This study conducts a system-level comparative evaluation of three NIST-standardized PQC digital signature schemes CRYSTALS-Dilithium2, Falcon-512, and SPHINCS+-128s to assess their suitability for secure e-Government document signing workflows. Methods: A simulation-based system-level evaluation is employed, wherein timing values are estimated from official NIST PQC parameter specifications and open-source benchmarks (PQClean, OQS), rather than measured from native cryptographic library executions. Experiments were conducted over 100 iterations, reporting mean ± standard deviation for key generation, signing, and verification times, alongside signature sizes and a RESTful API prototype demonstration. Results: Falcon-512 demonstrates the lowest estimated signing latency approximately five to six times faster than Dilithium2 and over fifty times faster than SPHINCS+-128s with the smallest signature size (666 bytes versus 2,420 and 7,856 bytes respectively). Dilithium2 provides a balanced trade-off between computational efficiency and signature robustness, while SPHINCS+-128s, despite its computational overhead, offers the strongest long-term security guarantees through its stateless hash-based construction. The RESTful API prototype confirms successful multi-scheme integration feasibility. Conclusion: This study recommends Falcon-512 for real-time mobile services, Dilithium2 for centralized server-side authentication, and SPHINCS+-128s for long-term archival security, providing evidence-based guidance for PQC adoption in national e-Government systems aligned with SPBE frameworks and NIST standards.